Teaching Materials for Applications and Studying in the Field of Interior Design in the Situation of Covid 19 - Phonsuwan, Kunakorn; Sangwachirapiban, Suebsai; Toongsi , Pakapong (DEC Journal : Art and Design, 2023)
The time when the situation of Covid-19 affects the lives of people around the world shows the change in society, technology and adaptation to living habits. Fields such as the professional field of interior design or education that have to adapt to the changing epidemic need to use online teaching and learning that consists of teachers, learners, content, learning materials, learning resources, learning management process communication system Yi team network system, assessment information, more diverse learning styles in the profession, working from home It is part of solving the problem to some extent. In the past, areas of learning were often focused on classrooms, but when such an epidemic emerged, the context and behavior of people in society changed. So is learning mixed work and technological connections, networks are therefore necessary to make education and various turbocharged can continue Mixed teaching and working Teachers must have teaching materials that can allow students to learn by themselves and build their own knowledge based on existing knowledge by coordinating with the theory of knowledge educational, for example, according to Bloom's theory (Bloom Taxonomy). The author has made teaching materials through applications due to the context of today's society. Everyone has their own smartphone. Students can search the application outside of class hours and review lessons outside of class time.